(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
Our present work describes the formulation and evaluation of an ocular deliver system of ofloxacin based on the concept of temperatureâ€and ionâ€activated in situ gelling system. A combination of Pluronic Fâ€127 and Pluronic Fâ€68 along with chitosan, (pHâ€sensitive polymer also acts as a permeation enhancer) was used in temperature and pHâ€triggered in situ gelling systems while gellan alone was used in ionâ€activated in situ gelling system. The formulation allows its easy instillation into the eye as a liquid (drops), forms transparent gel, and spreads over the corneal surface. At the formulation pH, transcorneal permeation profile of ofloxacin was comparable to that of in vitro release profile. In situ gelâ€forming ability of the developed systems significantly controls precorneal drainage as studied by gamma scintigraphy. Thus, increased residence time in the eye would help to increase the ocular bioavailability.The formulation was also found to be nonirritant and well tolerable. Cmax of in situ gelling formulation was found to be 1.5 times higher than marketed eye drops solution at the similar Tmax of 1 h.